Маркетингові дослідження ринку засобів рослинного походження гемостатичної групи - Червоненко, Наталія Михайлівна; Смойловська, Галина Павлівна; Мазулін, Олександр Владиленович; Андрухова, В. Д.; Бринза, Я. В.; Chervonenko, N. M.; Smoylovskaya, G. P.; Mazulin, A. V.; Andrukhova, V. D.; Brinza, Ya. V. (My University, 2013)
Проаналізовано вітчизняний фармацевтичний ринок гемостатичних фітопрепаратів. Здійснено структуризацію цих препаратів за АТС-класифікацією, встановлено асортимент і фірми-виробники лікарських засобів рослинного походження, їх розподіл за регіонами та соціально-економічними районами. Development of phytoneering approaches opened new potentials of application of herbal drugs and determined their place in modern medicine. Modern herbal pharmaceutical market has been found to be heterogeneous. Currently, the proportion of herbal drugs was up to 60 per cent of the drugs used to treat the nervous system, respiratory tract, cardiovascular system. At the same time, herbal medicines for the treatment of menstrual disorders, bleeding of various origins and diseases of the circulatory system virtually did not exist. In this context, domestic pharmaceutical market of hemostatic herbal drugs, was analyzed in accordance with the structuring of their ATC-classification. It was found that the range of this group of drugs was represented only by domestic manufacturing companies and consisted from 6 items and 15 positions. The leader in manufacturing enterprises was the central Ukraine with a specific weight of 60 per cent (9 positions). Also, the distribution of hemostatic manufacturers of herbal drugs by region and socio-economic areas has been studied. A range of herbal preparations with hemostatic effect in accordance with drugs’ forms and forms of production has been studied. The greatest in the proportion were solid dosage forms (73.3 per cent), presented only by leaves and grass; liquid dosage forms were produced in the form of tinctures and extracts (26.7 per cent). Studies had shown a lack of saturation of the domestic pharmaceutical market with herbal drugs of this group and indicated the prospects of the development of new hemostatic herbal drugs.
Marketing research of hemostatic drugs of plant origin
Keywords: маркетингові дослідження; гемостатичні засоби; фітопрепарати; marketing research; hemostatics; phytopreparation